1988
DOI: 10.1111/j.1399-3054.1988.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose responses of cytokinins

Abstract: Analysis of published data for the most widely used bioassays for cytokinins reveals that the dose responses are usually subsensitive, i.e. that S90/S10> 81. The data are. in general, insufficiently detailed and/or precise for the kinetics (cooperative, multiphasic or more complex) of the subsensitive responses to be determined. Genus‐and species‐specific differences in response type were found for callus growth, where the responses are ultrasensitive (S90/S10<81) for tabacco and Phaseolus Iunatus but mostly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 70 publications
2
8
1
Order By: Relevance
“…Like auxin, cytokinin generally inhibits root elongation (Stenlid, 1982;Nissen, 1988), but the hormone has been inferred to stimulate (Guttman, 1956;MacLeod, 1968), as well as to inhibit cell production (Butcher and Street, 1960;Van't Hof, 1968). We found that cytokinin reduced maximal strain rate significantly and so diminished the magnitude of cellular elongation.…”
Section: Comparison Of Cytokinin and Auxin Effects On Root Growthmentioning
confidence: 55%
“…Like auxin, cytokinin generally inhibits root elongation (Stenlid, 1982;Nissen, 1988), but the hormone has been inferred to stimulate (Guttman, 1956;MacLeod, 1968), as well as to inhibit cell production (Butcher and Street, 1960;Van't Hof, 1968). We found that cytokinin reduced maximal strain rate significantly and so diminished the magnitude of cellular elongation.…”
Section: Comparison Of Cytokinin and Auxin Effects On Root Growthmentioning
confidence: 55%
“…Previous models for plant hormone responses have used a single Michaelis-Menten equation to model dose-response relationships, with variable success (Weyers et al, 1987;Nissen, 1988aNissen, , 1988b. The basic refinement we have added is the coupling of two dose-response systems, a primary and a secondary system, in which the signal output from the primary system acts as the input signal for the secondary pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of detailed biochemical information, much of the research on hormone signal transduction in plants has been restricted to phenomenological studies in which the relationship between the dose of applied hormone and the increment of a chosen response has been quantified (for examples, see Nissen, 1985Nissen, , 1988aNissen, , 1988b. Koshland et al (1982) provided a general framework for considering the kinetics of signal-response relationships in biological systems.…”
mentioning
confidence: 99%
“…Cytokinins applied to roots are known to inhibit elongation (Stenlid, 1982;Nissen, 1988) and to stimulate radial expansion (Svensson, 1972;Kappler and Kristen, 1986), but the relationship between these responses is not understood. Our finding a bell-shaped dose-response curve for the stimulation of radial expansion but a sigmoidal curve for the inhibition of elongation suggests that the two responses are separate.…”
Section: Cytokinins and Cell Expansionmentioning
confidence: 99%